The Impact of Green Supply Chain Management Practices on Consumer Behaviour: An Amazon Ltd Case Study in France - Sakala, Kaluba (Graduate School of Business (GSB), 2025)
As environmental concerns continue to expand in relevance, businesses must shift their focus towards sustainability in their operations. Green supply chain management (GSCM) is a central strategy that seeks to diminish the environmental impact of procurement, manufacturing, transportation, and waste management. Despite this, there is a paucity of research exploring the connection between GSCM practices and consumer behaviour. This study addresses the gap by investigating the link between GSCM practices and consumer behaviour, with a specific emphasis on Amazon, a multinational retail company based in France. The theory of planned behaviour (TPB) is utilised as a conceptual framework, aiding in analysing the factors that drive consumer purchase decisions. The study adopted a qualitative methodology, conducting interviews with 15 environmentally conscious Amazon customers. Findings highlight that while consumers prioritise sustainability, other factors such as price, product availability, and convenience greatly influence their purchasing decisions. A significant discovery was the influence of knowledge and attitudes on consumer behaviour towards GSCM. The study also identified notable variations in consumers' understanding and perception of Amazon's GSCM practices. Consumer scepticism about Amazon's sustainability efforts was found to influence their purchasing decisions. By prioritising sustainability, companies can fulfil the demand for environmentally friendly products and influence consumer choices. However, it's important to acknowledge the limitations of this study, which primarily focuses on Amazon in France and may not be fully generalisable to other industries, geographical locations, and consumer demographics. Future research should delve into the impact of GSCM practices on consumer behaviour in a variety of contexts to provide a more comprehensive understanding. This study contributes to a more environmentally conscious future by understanding the factors that influence consumer decisions and addressing the challenges of implementing GSCM practices.